Quantitative characterization of micromixing simulation - Zhang, Zhiyi; Yim, ChaeHo; Lin, Min; Cao, Xudong (Université d'Ottawa | University of Ottawa, 2008)
Micromixers with floor-grooved microfluidic channels have been successfully demonstrated in experiment. In this work, we numerically simulated the mixing within the devices and used the obtained concentration versus channel length profiles to quantitatively characterize the process. It was found that the concentration at any given cross-section location of the microfluidic channel periodically oscillates along the channel length, in coordination with the groove-caused helical flow during the mixing, and eventually converges to the neutral concentration value of two the mixing fluids. With these data, the specific channel length required for each helical flow to complete, the mixing efficiency of the devices, and the total channel length required to complete a mixing were easily defined and quantified, and were used to directly and comprehensively characterize the micromixing. This concentration versus channel length profile-based characterization method was also demonstrated in quantitatively analyzing the micromixing within a classic T mixer. It has clear advantages over the traditional concentration image-based characterization method that is only able to provide qualitative or semiquantitative information about a micromixing, and is expected to find an increasing use in studying mixing and optimizing device structure through numerical simulations.
Keywords: rotational flow; mixing; microchannel flow; computational fluid dynamics; bioMEMS